Predicting herbage mass of Phleum pratense L. pastures with a disk meter - Virkajärvi, Perttu; Matilainen, Kaisa (Agricultural and Food Science, 1995)
A simple disk meter was calibrated for predicting the herbage mass (HM) of rotationally grazed pastures dominated by Phleum pratense L. in 1991-1992. A total of 696 paired observations were made on disk height (DH) and HM > 4 cm. The samples were classified for three different statuses: spring growth, post grazing and aftermath. In 1991 three different disk weights (c. 3.5, 5.0 and 6.5 kg/m2) were compared and the lightest disk was chosen for further studies in 1992. The variation in HM was adequately explained by linear models. There were only small differences between the predictive ability of different disk weights, the lightest disk having the highest r2 values. Post grazing and aftermath samples could be pooled, whilst spring growth samples needed a separate model. Year had no significant effect on the parameters of any model. The models chosen were: spring growth HM = -406.7 + 113.4(DH); r2 = 0.95, post grazing and aftermath HM = -629.1 + 122.1(DH); r2 = 0.88. The disk meter is a potential tool for predicting the HM of rotationally grazed timothy pastures.